FORENSIC CHARACTERISTICS OF ROAD TRAFFIC ACCIDENTS - А SECULAR TREND STUDY - Petrović, Ivan; Barać, Stevan; Filip,; Bošnjaković, Ksenija (Medicinski časopis, 2025)
Objective: Оbjective of work is to determine the forensic characteristics of road traffic accidents in territory of Raška District for period from 2009 to 2024.Material and methodology: Observational, cross-sectional epidemiological study, in which a retrospective analysis of the characteristics of traffic accidents in Raška District of Republic of Serbia over past sixteen years was performed.Results: Total number of road traffic accidents in observed period was 18.092. The research analyzed data from 2.129 road traffic accident participants who had a positive blood alcohol concentration. Largest number of road traffic accidents occurred in city of Kraljevo, outside of a populated area. Largest percentage of participants were motor vehicle drivers (88.54%), male (93.2%), with an average age of around 40 years. Seasonal relationship was observed in occurrence of road traffic accidents (August, September), as well as a higher incidence on weekends. Participants who were in the stage of heavy drinking more often suffered serious bodily injury, while participants who were in a state of intoxication and light drinking more often suffered minor bodily injury.Conclusion: Road traffic accidents in the Raška District are the result of a combination of several factors, including driving under the influence of alcohol, traffic infrastructure, high population density in certain cities and specific characteristics of Ibar Highway.
Keywords: traffic accident, injuries, drivers, alcohol